The impact of emotional states on relations with the family in people with inflammatory bowel disease - Jodłowska-Jędrych, Barbara; Jędrych, Marian; Ruta, Ewelina; Binduga, Urszula; Stawecka-Wiatrowska, Anna (Polish Journal of Public Health, 2012)
Introduction. Inflammatory bowel disease is distinguished by two phenotypically distinct diseases: ulcerative colitis and Crohn’s disease. This is a group of chronic diseases, which, as a diffuse process, influence the most distal colon and small intestines, as well as other areas of the colon. These diseases are characterized by spontaneous relapses and remissions of unknown etiology. Aim. The aim of this study was to present and describe the impact of emotional states on family relationships in people with inflammatory bowel disease. Material and methods. The study was conducted at the Department of Gastroenterology, The Autonomous Public Clinical Hospital No. 4 in Lublin and at the Department of Gastroenterology of Cardinal Stefan Wyszynski Provincial Specialist Hospital in Lublin, from November 2009 to May 2010. The study involved 98 patients with Crohn’s disease and ulcerative colitis. Statistical analysis included primarily verification of statistical hypotheses based on independent tests of Pearson’s χ2 and logistic analysis. Results. A significant relationship between the occurrence of depression, anxiety, hopelessness, lack of energy for life, despair and depression as an emotional state and the kind of relationship with the family was confirmed. Conclusions. Logistic regression analysis allowed for choosing of two from among many features: asthenia, and relationships with family, having a significant impact on the occurrence of depression. Inflammatory bowel disease destroys the existing order of life and presents man with the feelings not previously experienced.